2018
DOI: 10.1002/jib.487
|View full text |Cite
|
Sign up to set email alerts
|

Variation in gluten protein and peptide concentrations in Belgian barley malt beers

Abstract: Gluten is the main family of storage proteins found in barley. During malting and brewing, some of the barley malt's proteinaceous material is hydrolysed into peptides or to amino acids. Most of the gluten proteins are removed with the spent grains and with hot‐ and cold‐breaks. However, some gluten proteins and especially gluten‐derived peptides can remain throughout the brewing process and will hamper the gluten‐free (≤20 ppm) status of the beer. In this work, three production batches (a, b and c) of 51 Belg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Considering that ale yeast is used for gueuze beer production, results from the present research are completely in agreement with those reported with Belgian beers. Indeed, no correlation exists between the original extract of barley beers and gluten content [ 29 ], which we confirmed. As a whole, and supported by the literature, both the main ingredients as well as the yeasts used are relevant contributors to the gluten content of beers.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Considering that ale yeast is used for gueuze beer production, results from the present research are completely in agreement with those reported with Belgian beers. Indeed, no correlation exists between the original extract of barley beers and gluten content [ 29 ], which we confirmed. As a whole, and supported by the literature, both the main ingredients as well as the yeasts used are relevant contributors to the gluten content of beers.…”
Section: Discussionsupporting
confidence: 67%
“…Similar inferences were made in 51 commercial Belgian barley malt beers, measured by the same kits. R5 competitive ELISA identified less than half the number of GF beer than did direct assay (18 vs. 45) [ 29 ]. However, in the present approach, the noncompetitive kit comes from a different manufacturer and is a direct ELISA and thus not based on sandwich methodology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations